Transplantation of Half-Cut Tuber Seedlings Provides Enhanced Yields Over Conventional Sprouted-Vine Planting in Sweet Potato Cultivar “Murasakimasari” - Katsuki Adachi; Mitsuho Sugimoto; Masaaki Omine; Nobuyuki Sawamura; Takanori Ishii; Tooru Kobayashi (Plant Production Science, 2011)
Seed tubers of sweet potato cultivar “Murasakimasari”, the weights of which range from 30 to 100 g, were cut in half at a right angle to the long axis of the tuber, and planted in cell trays (cell size: 55 mm×55 mm×height 62.5 mm, 50 cells in a 30 cm×60 cm tray) with commercial soil mixes. The planted half-cut tubers in cell trays were incubated at 25ºC under natural sunlight conditions in a glasshouse for 3 to 4 wk to raise half-cut tuber seedlings. Half-cut tuber seedlings were transplanted on 28 March (TST1) or on 24 April (TST2), whole seed tubers were directly planted on 26 March (DP), conventional sprouted vines were planted on 30 April (VP) in an experimental field. The highest tuber yield was obtained from TST1, followed by TST2 and VP, and DP in this order. Deformed tubers emerged from the TST1 and TST2 groups, at a rate of 3.0% and 6.7% of daughter tubers, respectively. A regional trial in a farmer’s field revealed that the tuber yields and numbers of tubers per plant were higher in TST (tuber seedling transplanting) than those in VP (vine planting). The statistical analysis of the 2 field experiments suggests that transplantation of half-cut tuber seedlings provides enhanced yields over conventional sprouted-vine planting.